Alkali borosilicate glass, bent glass, laminated glass, building window glass, and vehicle window glass
By adjusting the ratio of tri-coordinated boron to tetracoordinated boron in the glass, the glass is grey, and the problem of using harmful elements Se and CoO in the prior art is solved, and the excellent thermal insulation and appearance design of the glass is achieved.
Patent Information
- Application Number
- CN202380048199.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-20
- Filing Date
- 2023-06-09
- Publication Date
- 2025-02-28
AI Technical Summary
The Se and CoO components used in the prior art when giving gray to glass are harmful to the human body, and the gray color is weak and cannot meet the design requirements.
By adjusting the ratio of tri-coordinated boron to tetra-coordinated boron in the glass, the glass is grey, and the effect of excellent appearance design is achieved without the use of harmful elements Se and CoO.
It realizes that glass has excellent thermal insulation and design properties without using harmful elements, and is suitable for vehicle window glass and building window glass.
Smart Images

Figure CN119546560A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to alkali borosilicate glass, bent glass, laminated glass, building window glass and vehicle window glass. Background Art
[0002] In recent years, from the perspective of energy saving, glass for vehicles, such as automobiles, is required to have heat-insulating properties. By using glass with high heat-insulating properties for vehicles, the temperature rise in the vehicle caused by sunlight can be suppressed, and the cooling load can be reduced.
[0003] In addition, from the viewpoint of excellent design and privacy protection inside the vehicle, gray glass is required for vehicle glass. Patent Documents 1 and 2 disclose that gray glass can be obtained by adding CoO or Se as a coloring component to soda-lime-silica glass.
[0004] In addition to the above characteristics, from the perspective of fuel efficiency and power consumption, vehicle glass is required to be lighter. As vehicle glass, alkali borosilicate glass can be cited as a glass with a smaller specific gravity than soda-lime-silica glass as ordinary glass.
[0005] Alkali borosilicate glass has a low specific gravity and excellent flystone resistance, so it is preferably used as glass for vehicles. Patent Document 3 discloses glass for vehicles using alkali borosilicate glass. Patent Document 4 discloses that gray glass is obtained by adding CoO to alkali borosilicate glass. Patent Document 5 discloses that gray glass is obtained by adding Fe2O3, Er2O3, etc. to alkali borosilicate glass.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Laid-Open No. 9-301736
[0009] Patent Document 2: Japanese Patent Application Publication No. 2001-019470
[0010] Patent Document 3: U.S. Patent Application Publication No. 2018 / 0194114
[0011] Patent Document 4: Japanese Patent Application Laid-Open No. 7-109147
[0012] Patent Document 5: Japanese Patent Application Laid-Open No. 4-280834 Summary of the invention
[0013] Problems to be solved by the invention
[0014] In Patent Documents 1, 2, and 4, Se and CoO are used to impart gray color to glass. However, since these components are harmful to the human body, it is desired to impart gray color to glass without using these components.
[0015] In addition, in the alkali borosilicate glass described in Patent Document 5, Se and CoO are not essential components, but gray color rendering is weak, which is insufficient from the viewpoint of appearance design.
[0016] In view of the above problems, the object of the present invention is to provide an alkali borosilicate glass, curved glass, laminated glass, which has excellent heat insulation and excellent appearance design without using harmful elements, and a building window glass or a vehicle window glass using the alkali borosilicate glass or the laminated glass.
[0017] Means used to solve problems
[0018] The present inventors have found that a gray color can be imparted to glass by adjusting the ratio of tricoordinate boron to tetracoordinate boron in glass, thereby completing the present invention.
[0019] That is, the present invention is as follows.
[0020] [1] An alkali borosilicate glass, wherein the content of total iron in the alkali borosilicate glass converted to Fe2O3 is 0.03% or more, measured in mole % based on oxides, the ratio of tricoordinate boron to the total amount of tricoordinate boron and tetracoordinate boron is 61% or less, the alkali borosilicate glass contains substantially no Se and CoO, the solar energy transmittance Te of the alkali borosilicate glass as specified in ISO-9050:2003 is 90% or less when the thickness is converted to 2.0 mm, the dominant wavelength Dw of the alkali borosilicate glass measured using the standard C light source specified in JIS Z 8701:1999 is 520 nm or more and 574 nm or less, and the excitation purity Pe of the alkali borosilicate glass measured using the standard C light source specified in JIS Z 8701:1999 is 4.0% or less.
[0021] [2] The alkali borosilicate glass as described in [1], wherein when the thickness is converted to 2.0 mm, the ratio (Tv / Te) of the visible light transmittance Tv of the alkali borosilicate glass as defined by ISO-9050:2003 obtained using a D65 light source to the solar energy transmittance Te of the alkali borosilicate glass as defined by ISO-9050:2003 is greater than 1.05.
[0022] [3] The alkali borosilicate glass according to [1] or [2], wherein the visible light transmittance Tv of the alkali borosilicate glass as defined in ISO-9050:2003 obtained using a D65 light source is 75% or more when the thickness is converted to 2.0 mm.
[0023] [4] The alkali borosilicate glass as described in [1] or [2], wherein the visible light transmittance Tv of the alkali borosilicate glass defined by ISO-9050:2003 obtained using a D65 light source is less than 75% when the thickness is converted to 2.0 mm.
[0024] [5] The alkali borosilicate glass as described in any one of [1] to [4], wherein the content of total iron in the alkali borosilicate glass calculated as Fe2O3 is 0.040% or more and 0.60% or less, in terms of mol% based on oxides.
[0025] [6] The alkali borosilicate glass according to any one of [1] to [5], wherein the Young's modulus of the alkali borosilicate glass is 65 GPa or more.
[0026] [7] The alkali borosilicate glass according to any one of [1] to [6], wherein the glass viscosity is 10 11 [dPa·s] at temperature T 11 Below 640°C.
[0027] [8] The alkali borosilicate glass as described in any one of [1] to [7], wherein the alkali borosilicate glass comprises, in terms of mol % based on oxides: 70%≤SiO2≤80%, 8.0%≤B2O3≤20%, 1.0%≤Al2O3≤5.0%, 0.0%≤Li2O≤5.0%, 2.0%≤Na2O≤10%, 0.0%≤K2O≤5.0%, 0.0%≤MgO≤5.0%, 0.0%≤CaO≤5.0%, 0.0%≤SrO≤5.0%, 0.0%≤BaO≤5.0%, SiO2+B2O3+Al2O3≥89%, and Li2O+Na2O+K2O≥5.0%.
[0028] [9] An alkali borosilicate glass as described in any one of [1] to [8], wherein the content of total iron converted to Fe2O3 in the alkali borosilicate glass is greater than 0.040% and less than 0.60% in terms of molar % based on oxide, and the mass proportion of divalent iron converted to Fe2O3 in the total iron converted to Fe2O3 is greater than 10%.
[0029]
[10] The alkali borosilicate glass according to any one of [1] to [9], wherein the alkali borosilicate glass contains Li2O.
[0030]
[11] A curved glass comprising the alkali borosilicate glass according to any one of [1] to
[10] .
[0031]
[12] A laminated glass comprising a first glass plate, a second glass plate and an intermediate film sandwiched between the first glass plate and the second glass plate, wherein the first glass plate is the alkali borosilicate glass described in any one of [1] to
[10] or the bent glass described in
[11] .
[0032]
[13] The laminated glass according to
[12] , wherein the second glass plate is the alkali borosilicate glass according to any one of [1] to
[10] or the bent glass according to
[11] .
[0033]
[14] The laminated glass according to
[12] , wherein the second glass plate is an alkali aluminosilicate glass containing 1.0% or more of Al2O3 in terms of molar percentage on an oxide basis.
[0034]
[15] The laminated glass according to
[12] , wherein the second glass plate is an alkali aluminoborosilicate glass containing 1.0% or more of Al2O3 and 1.0% or more of B2O3 in terms of molar percentage on an oxide basis.
[0035]
[16] The laminated glass according to
[12] , wherein the second glass plate is chemically strengthened glass.
[0036]
[17] The laminated glass according to
[12] , wherein the second glass plate is soda-lime glass.
[0037]
[18] A vehicle window glass comprising the alkali borosilicate glass according to any one of [1] to
[10] or the bent glass according to
[11] .
[0038]
[19] A vehicle window glass comprising the laminated glass according to any one of
[12] to
[17] .
[0039]
[20] A window glass for building, comprising the alkali borosilicate glass according to any one of [1] to
[10] or the bent glass according to
[11] .
[0040] Effects of the Invention
[0041] According to the present invention, there are provided alkali borosilicate glass, curved glass, laminated glass having excellent heat shielding properties and excellent design without using harmful elements, and architectural window glass or vehicle window glass using the alkali borosilicate glass or laminated glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 It is a graph showing the transmission spectra of Examples 1, 6, 9 and 11.
[0043] Figure 2 Graph showing the relationship between the ratio of tricoordinate boron and the main wavelength Dw.
[0044] Figure 3 This is a graph showing the relationship between the ratio of tricoordinate boron and the excitation purity Pe.
[0045] Figure 4 This is a cross-sectional view of an example of a laminated glass according to an embodiment of the present invention.
[0046] Figure 5 This is a conceptual diagram showing a state in which a laminated glass according to an embodiment of the present invention is used as a vehicle window glass.
[0047] Figure 6 for Figure 5 Magnified view of the S portion.
[0048] Figure 7 for Figure 6 Section view along line YY. DETAILED DESCRIPTION
[0049] The following is a detailed description of the embodiments of the present invention. In addition, in the following drawings, components and parts that play the same role are marked with the same symbols for description, and repeated descriptions are sometimes omitted or simplified. In addition, the embodiments described in the drawings are schematically illustrated to clearly illustrate the present invention, and do not necessarily accurately represent the size and scale of the actual product.
[0050] In this specification, "glass does not substantially contain" a certain component means that it does not contain it except for inevitable impurities, and the component is not actively added. Specifically, it means that the content of these components in the glass is about 10 mol ppm or less. It should be noted that, with respect to Se and CoO, "substantially does not contain" means that the content of these components in the glass is 1 mol ppm or less.
[0051] The alkali borosilicate glass of the present embodiment is characterized in that, measured in molar % based on oxide, the total iron content converted to Fe2O3 in the alkali borosilicate glass is greater than 0.03%, the proportion of tricoordinate boron to the total amount of tricoordinate boron and tetracoordinate boron is less than 61%, the alkali borosilicate glass does not substantially contain Se and CoO, and when the thickness is converted to 2.0 mm, the solar transmittance Te of the alkali borosilicate glass is less than 90%, the main wavelength Dw is greater than 520 nm and less than 574 nm, and the excitation purity Pe is less than 4.0%.
[0052] In the alkali borosilicate glass (hereinafter sometimes referred to as glass) of the present embodiment, Fe2O3 is an essential component, and is contained for heat insulation and to give the glass a gray color. In the glass of the present embodiment, the total iron content converted to Fe2O3 is 0.03% or more in terms of mole % based on oxides. The total iron content converted to Fe2O3 mentioned here refers to the total iron content containing FeO as an oxide of divalent iron and Fe2O3 as an oxide of trivalent iron.
[0053] The glass of this embodiment has a total iron content of 0.03% or more calculated as Fe2O3, which can suppress a decrease in visible light transmittance, enable the manufacture of glass suitable for vehicle window glass, etc., and facilitate melting of raw materials during manufacture.
[0054] When the content of total iron converted to Fe2O3 of the glass of the present embodiment is less than 0.03%, it may not be used for applications requiring heat insulation. In addition, in order to manufacture glass, it is sometimes necessary to use expensive raw materials with less iron content. In addition, when the content of total iron converted to Fe2O3 is less than 0.03%, when the glass is melted, it is possible that excessive heat radiation reaches the bottom of the melting furnace, exerting a load on the melting furnace. In the glass of the present embodiment, the content of total iron converted to Fe2O3 is preferably 0.040% or more, more preferably 0.060% or more, further preferably 0.080% or more, particularly preferably 0.10% or more, and most preferably 0.12% or more.
[0055] In addition, iron has coloring to the light in the visible light region. Therefore, when the content of total iron converted to Fe2O3 is too much, the visible light transmittance Tv is reduced, so it is not preferred for vehicle windshields and door glasses. In addition, the excitation purity Pe described later becomes high, and the color (color taste) of the glass becomes darker. As a result, the color of the glass is not gray, so it is not preferred. The content of total iron converted to Fe2O3 in the glass of the present embodiment is preferably less than 0.60%, more preferably less than 0.50%, further preferably less than 0.40%, particularly preferably less than 0.30%, and most preferably less than 0.25%. That is, in the glass of the present embodiment, in terms of the mole % of the oxide basis, the content of total iron converted to Fe2O3 is, for example, more than 0.03% and less than 0.60%.
[0056] In the glass of the present embodiment, the ratio of tricoordinate boron to the total amount of tricoordinate boron and tetracoordinate boron is 61% or less. The present inventors have found that by setting the ratio of tricoordinate boron to the total amount of tricoordinate boron and tetracoordinate boron contained in the glass to 61% or less, the glass shows gray even without Se and CoO, and can obtain glass with excellent appearance design.
[0057] Boron can adopt tri-coordinate or tetra-coordinate oxygen coordination number in glass. Tetra-coordinate boron enters the glass skeleton to form a tetrahedral structure. At this time, since the tetrahedral structure is negatively charged, the charge is compensated by alkali metal ions and alkaline earth metal ions. Therefore, tetra-coordinate boron hardly produces non-bridging oxygen, forming a three-dimensional glass structure. On the other hand, it is known that tri-coordinate boron has non-bridging oxygen in glass and presents a planar structure such as a ring structure (Boroxol ring).
[0058] Figure 1 Graph showing the transmission spectra of the glass plates of Examples 1, 6, 9 and 11 described later. The glass of this embodiment contains boron and iron. Figure 1 As shown in the transmission spectrum of Example 11, the light absorption spectrum based on Fe ions in the wavelength range of 400nm to 650nm is flatter than that of the soda-lime-silicon glass of Example 1. However, by increasing the proportion of tricoordinated boron, as shown in Examples 6 and 9, a tendency of increasing two broad absorptions centered around wavelengths of 350nm and 500nm was observed. It is believed that the broad absorption around the wavelength of 500nm is caused by the Fe contained in the glass. 2+ with Fe 3+ The intervalence charge transfer transition (IVCT) between Fe and Fe occurs by increasing the proportion of tricoordinated boron. 2+ with Fe 3+ The mechanism of intervalence charge transfer transition between Fe and Fe is not clear, but it is believed that the planar structure generated by the presence of tricoordinate boron produces a cluster structure in which Fe in the glass is close to each other. 2+ with Fe 3+ The distance between them becomes closer, which easily causes charge transfer transition.
[0059] like Figure 1 As shown, as the ratio of tri-coordinated boron increases, the transmittance of light in the visible light region decreases significantly, which greatly affects the color of the glass. Figure 2 This is a graph showing the relationship between the main wavelength Dw and the ratio of tricoordinate boron measured using the standard C light source specified in JIS Z 8701:1999 for the glasses of the examples and comparative examples described later. Figure 2 As shown, it can be seen that as the ratio of tricoordinate boron increases, that is, as the transmittance in the visible light region due to IVCT decreases, the main wavelength Dw increases, and the glass exhibits a brown color.
[0060] in addition, Figure 3 This is a graph showing the relationship between the excitation purity Pe and the ratio of tricoordinate boron measured using the standard C light source specified in JIS Z 8701:1999 for the glasses of the examples and comparative examples described later. Figure 3As shown, it can be seen that when the ratio of tricoordinate boron increases, the excitation purity Pe also increases. As mentioned above, controlling the ratio of tricoordinate boron is important for obtaining glass with excellent appearance design. If the ratio of tricoordinate boron is less than 61%, the main wavelength Dw is less than 574nm, and achromatic gray glass with low excitation purity Pe can be achieved.
[0061] In addition, the glass of the present embodiment has a gray color and an improved Young's modulus by reducing the proportion of tricoordinate boron, making it more suitable for use in vehicles and buildings. The reason for the improvement of the Young's modulus is that the proportion of tricoordinate boron is reduced and the proportion of tetracoordinate boron is increased, thereby reducing non-bridging oxygen and forming a dense structure, which contributes to the increase of the ion filling rate and bond dissociation energy of the Young's modulus.
[0062] Therefore, in this embodiment, the ratio of tricoordinate boron to the total amount of tricoordinate boron and tetracoordinate boron is 61% or less, preferably 60% or less, more preferably 59% or less, further preferably 58% or less, particularly preferably 56% or less, and most preferably 54% or less.
[0063] In addition, the ratio of tricoordinate boron relative to the total amount of tricoordinate boron and tetracoordinate boron is preferably more than 20%. By the ratio of tricoordinate boron being more than 20%, the flying stone resistance of glass can be improved. As the reason for improving flying stone resistance, due to the increase in the ratio of tricoordinate boron, non-bridging oxygen increases compared with tetracoordinate boron, and tricoordinate boron adopts a planar structure, so the network structure of glass becomes loose. As a result, it is believed that when flying stones collide with glass, due to the densification of the network structure of glass, the energy caused by the collision is consumed, the occurrence of cracks is suppressed, and flying stone resistance is improved. The ratio of tricoordinate boron relative to the total amount of tricoordinate boron and tetracoordinate boron is more preferably more than 30%, further preferably more than 35%, further preferably more than 37%, particularly preferably more than 39%, and most preferably more than 41%. That is, the ratio of tricoordinate boron relative to the total amount of tricoordinate boron and tetracoordinate boron is, for example, more than 20% and less than 61%.
[0064] The ratio of tricoordinate boron to tetracoordinate boron can be adjusted by adjusting the composition of the glass, and more specifically, by appropriately adjusting the contents of alkali metal oxides, alkaline earth metal oxides, and Al2O3.
[0065] As described above, tetracoordinated boron assists the charge through alkali metal ions and exists in the glass as a tetrahedral structure. That is, when alkali metal oxides are added to the glass, boron is consumed in the tetracoordinate formation, and the boron that is not coordinated with the alkali metal ions exists in a tricoordinate form. Therefore, by increasing the content of alkali metal oxides, the proportion of tricoordinated boron in the glass decreases, and the gray color of the glass becomes stronger.
[0066] In addition, the content of Al2O3 needs to be considered at this time. It is known that Al takes a coordination number of 4 to 6 in glass according to oxygen. Among them, four-coordinated Al forms a glass structure as a tetrahedral structure. Four-coordinated Al has the same negative charge as four-coordinated boron, so the charge is compensated by alkali metal ions. At this time, the alkali metal ions present in the glass coordinate to Al preferentially over boron. Specifically, for example, in the case of a glass in which the content ratio of Al2O3 to alkali metal oxide and B2O3 is 1:1:1, almost all of the alkali metal oxide is consumed in the tetracoordination of Al. In the absence of charge compensation by alkali metal ions, boron exists in a tri-coordinated form, so in the case of the above ratio, almost all of the boron in the glass exists in a tri-coordinated form.
[0067] In addition, like alkali metal oxides, alkaline earth metal oxides also affect the coordination number of boron. In particular, ions with lower electronegativity are more likely to react with boron to increase tetracoordinated boron, so there is a tendency for the ratio of tetracoordinated boron to increase in the order of Ba, Sr, Ca, and Mg, which have lower electronegativity.
[0068] Therefore, the ratio of tricoordinate boron to tetracoordinate boron is adjusted by adjusting the contents of alkali metal oxides, alkaline earth metal oxides, and Al2O3.
[0069] The ratio of tricoordinate boron to tetracoordinate boron in glass can be measured by nuclear magnetic resonance (NMR). Specifically, it can be measured by the method described in the examples described below.
[0070] When the thickness is converted to 2.0 mm, the solar transmittance Te of the glass of the present embodiment as specified by ISO-9050:2003 is 90% or less. If Te is 90% or less, the heat insulation of the glass is excellent. Te is preferably 88% or less, more preferably 86% or less, further preferably 84% or less, particularly preferably 82% or less, and most preferably 80% or less. The lower limit of Te is not particularly limited, and is usually 30% or more, preferably 32% or more, more preferably 34% or more, and particularly preferably 36% or more. That is, Te is, for example, 30% or more and 90% or less.
[0071] The glass of this embodiment has a dominant wavelength Dw of 520 nm or more and 574 nm or less measured by a standard C light source specified in JIS Z 8701: 1999. Dw is preferably 525 nm or more, more preferably 530 nm or more, further preferably 535 nm or more, and most preferably 540 nm or more. In addition, Dw is preferably 573 nm or less, more preferably 570 nm or less, further preferably 567 nm or less, and most preferably 565 nm or less.
[0072] The glass of this embodiment has an excitation purity Pe of 4.0% or less measured by a standard C light source specified in JIS Z 8701:1999. Pe is preferably 3.5% or less, more preferably 3.0% or less, further preferably 2.5% or less, particularly preferably 2.0% or less, and most preferably 1.5% or less. In addition, the lower limit of Pe is not particularly limited, but is usually 0.1% or more. That is, Pe is, for example, 0.1% or more and 4.0% or less.
[0073] When Dw and Pe are within the above ranges, the glass becomes gray and exhibits excellent design properties.
[0074] <Glass composition>
[0075] The glass of this embodiment does not substantially contain Se and CoO. Se and CoO are generally used as components that impart gray to glass, but these components are harmful to the human body. In this embodiment, as described above, by adjusting the ratio of tricoordinate boron to tetracoordinate boron, it is possible to impart gray to the glass, so that glass having excellent appearance design properties can be obtained without adding Se and CoO, which are harmful components to the human body.
[0076] In terms of molar percentage based on oxides, the glass of this embodiment preferably contains: 70%≤SiO2≤80%, 8.0%≤B2O3≤20%, 1.0%≤Al2O3≤5.0%, 0.0%≤Li2O≤5.0%, 2.0%≤Na2O≤10%, 0.0%≤K2O≤5.0%, 0.0%≤MgO≤5.0%, 0.0%≤CaO≤5.0%, 0.0%≤SrO≤5.0%, 0.0%≤BaO≤5.0%, SiO2+B2O3+Al2O3≥89%, Li2O+Na2O+K2O≥5.0%.
[0077] Hereinafter, the preferred composition range of each component in the glass of the present embodiment will be described. It should be noted that, unless otherwise specified, the composition range of each component is expressed in terms of molar percentage based on oxides.
[0078] SiO2 contributes to improving the Young's modulus, and is therefore a component that easily ensures the strength required for vehicle use, construction use, etc. In the present embodiment, the content of SiO2 is preferably 70% or more and 80% or less.
[0079] By having a SiO2 content of 70% or more, it is easy to reduce the specific gravity of the glass and also ensure weather resistance. In addition, the average linear expansion coefficient is suppressed from becoming larger, and the thermal cracking of the glass is suppressed. The SiO2 content is more preferably 72% or more, further preferably 73% or more, and particularly preferably 74% or more.
[0080] In addition, by SiO2 content being below 80%, in addition to suppressing the increase of viscosity when glass melts, glass manufacturing becomes easy, the formability of vehicle window glass, particularly windshield, etc. is improved. SiO2 content is more preferably below 79%, further preferably below 78%, and particularly preferably below 77%.
[0081] As described above, B2O3 controls the optical properties of glass, reduces the specific gravity of glass, and also contributes to the improvement of glass strength and solubility. In this embodiment, the content of B2O3 is preferably 8.0% or more and 20% or less.
[0082] The content of B2O3 is 8.0% or more, which can control the optical properties of the glass, and can also contribute to the reduction of the specific gravity of the glass, the improvement of the glass strength and the improvement of the solubility. The content of B2O3 is more preferably 8.5% or more, further preferably 9.0% or more, particularly preferably 9.5% or more, and most preferably 10% or more.
[0083] In addition, when B2O3 is 20% or less, alkali elements are not easily volatilized during melting and forming of glass, and the glass quality can be suppressed from being degraded. In addition, acid resistance and alkali resistance can be improved. The content of B2O3 is more preferably 18% or less, further preferably 16% or less, particularly preferably 15% or less, and most preferably 14% or less.
[0084] In the present embodiment, the content of Al2O3 is preferably 1.0% or more and 5.0% or less. When Al2O3 is 1.0% or more, four-coordinated Al2O3 coordinated by alkali metal is generated, thereby reducing the non-bridging oxygen in the glass, and improving the weather resistance, weathering resistance (resistance to weathering) and chemical durability. In addition, in addition to the average linear expansion coefficient not becoming too large and being able to suppress the thermal cracking of the glass, chemical strengthening treatment using ion exchange can also be performed. The content of Al2O3 is more preferably 1.1% or more, further preferably 1.3% or more, particularly preferably 1.5% or more, and most preferably 1.7% or more.
[0085] In addition, by Al2O3 being 5.0% or less, the content of alkali metal coordinated with boron increases, and the proportion of tri-coordinated boron can be reduced. In addition, in addition to suppressing the viscosity increase during glass melting and making glass manufacturing easier, the formability of vehicle window glass, especially windshield, etc. is also improved. The content of Al2O3 is more preferably 4.5% or less, further preferably 4.0% or less, particularly preferably 3.5% or less, and most preferably 3.0% or less.
[0086] Li2O is a component that greatly improves the solubility of glass by adding a small amount. In addition, it is a component that easily increases Young's modulus and contributes to the linear expansion coefficient of glass. In addition, by coordinating lithium ions with boron, the proportion of tetracoordinated boron can also be increased. In this embodiment, the content of Li2O is preferably 0.0% or more and 5.0% or less.
[0087] By containing Li2O, the viscosity of the glass is reduced, thereby improving the formability of vehicle window glass, especially windshield, etc. When the glass of this embodiment contains Li2O, its content is preferably 0.50% or more, more preferably 1.0% or more, further preferably 1.5% or more, particularly preferably 1.7% or more, and most preferably 2.0% or more.
[0088] By the content of Li2O being below 5.0%, in addition to being able to suppress the occurrence of devitrification or phase separation during glass manufacturing and making the manufacture of glass easier, it is also possible to reduce the linear expansion coefficient and suppress the thermal cracking of glass. In addition, since the lithium raw material price is high, it also has the effect of suppressing the cost of raw materials. The content of Li2O is more preferably below 4.5%, further preferably below 4.0%, particularly preferably below 3.5%, and most preferably below 3.0%.
[0089] Na2O is a component that improves the solubility of glass, and is also a component that easily increases Young's modulus and contributes to the linear expansion coefficient of glass. In addition, in addition to being able to coordinate with boron and increase the proportion of tetracoordinated boron, it is also possible to improve the strength of glass by chemically strengthening treatment using ion exchange with K ions. In this embodiment, the content of Na2O is preferably 2.0% or more and 10% or less.
[0090] By containing 2.0% or more of Na2O, the viscosity of the glass is reduced, so the formability of vehicle window glass, especially windshield, is improved. The content of Na2O is more preferably 3.5% or more, further preferably 4.0% or more, particularly preferably 4.5% or more, and most preferably 5.0% or more.
[0091] When the content of Na2O is 10% or less, the linear expansion coefficient can be reduced and the thermal cracking of the glass can be suppressed. In addition, since the weathering resistance of the glass is improved, it is suitable as glass exposed to the atmosphere for a long time, such as vehicle window glass and building window glass. The content of Na2O is more preferably 9.0% or less, further preferably 8.5% or less, particularly preferably 8.0% or less, and most preferably 7.5% or less.
[0092] K2O is a component that improves the solubility of glass, increases Young's modulus, and contributes to the linear expansion coefficient of glass. In the present embodiment, the content of K2O is preferably 0.0% or more and 5.0% or less.
[0093] By containing K2O, the viscosity of the glass is reduced, so the formability of vehicle window glass, especially windshield, is improved. In addition, it can also coordinate with boron to increase the proportion of tetracoordinated boron. On the other hand, K2O has the effect of increasing the linear expansion coefficient and specific gravity compared with Li2O and Na2O, so it is preferably added in a trace amount compared with Li2O and Na2O. In the case of containing K2O, its content is more preferably 0.10% or more, further preferably 0.20% or more, particularly preferably 0.30% or more, extremely preferably 0.40% or more, and most preferably 0.50% or more.
[0094] When the content of K2O is 5.0% or less, the increase of the linear expansion coefficient and the specific gravity can be suppressed. The content of K2O is more preferably 4.0% or less, further preferably 3.5% or less, particularly preferably 3.0% or less, and most preferably 2.5% or less.
[0095] MgO is a component that promotes the melting of glass raw materials and improves weather resistance, weathering resistance and Young's modulus. In addition, as mentioned above, due to the high electronegativity, the proportion of tri-coordinated boron can be increased. In the present embodiment, the content of MgO is preferably 0.0% or more and 5.0% or less. In the case of containing MgO, in order to suppress the excessive proportion of tri-coordinated boron, its content is more preferably 0.20% or more, further preferably 0.50% or more, particularly preferably 0.70% or more, and most preferably 1.0% or more.
[0096] In addition, if the content of MgO is below 5.0%, the glass is not easy to lose transparency and the viscosity when the glass is melted is increased, and the glass is easily manufactured, and the formability of vehicle window glass, particularly windshield, etc. is also improved. In addition, the ratio of tri-coordinated boron can be suppressed to be low. The content of MgO is more preferably below 4.0%, further preferably below 3.5%, particularly preferably below 3.0%, and most preferably below 2.5%.
[0097] CaO is a component that improves the solubility of glass raw materials. In addition, as mentioned above, due to its high electronegativity, the proportion of tri-coordinated boron can be increased. In the present embodiment, the content of CaO is preferably 0.0% or more and 5.0% or less. In the case of containing CaO, its content is more preferably 0.20% or more, further preferably 0.50% or more, particularly preferably 0.70% or more, and most preferably 1.0% or more. Thus, the solubility of glass raw materials, vehicle window glass, especially the formability of windshields, etc. are improved.
[0098] In addition, by making the content of CaO 5.0% or less, it is possible to avoid an increase in glass density, suppress low brittleness, and maintain strength. It is also possible to suppress the proportion of tri-coordinated boron to a low level. The content of CaO is more preferably 4.0% or less, further preferably 3.5% or less, particularly preferably 3.0% or less, and most preferably 2.5% or less.
[0099] SrO is a component that improves the solubility of glass raw materials. In addition, as mentioned above, since the electronegativity is lower than that of Mg and Ca, the proportion of tetracoordinated boron can be increased. On the other hand, the specific gravity of the glass increases, the brittleness decreases, and the strength of the glass may decrease, so it is preferred not to actively contain SrO. In the case of containing SrO in the present embodiment, its content is more preferably 0.10% or more, further preferably 0.20% or more, particularly preferably 0.30% or more, extremely preferably 0.40% or more, and most preferably 0.50% or more. Thus, the solubility of the raw materials of the glass, the formability of vehicle window glass, especially windshield, etc. is improved.
[0100] In addition, the content of SrO is preferably 5.0% or less. By making the content of SrO 5.0% or less, the increase in the specific gravity of the glass can be suppressed. In addition, the increase in the density of the glass is avoided, the low brittleness is suppressed, and the strength is maintained. The content of SrO is more preferably 4.0% or less, further preferably 3.0% or less, particularly preferably 2.0% or less, and most preferably 1.0% or less. That is, the content of SrO is preferably 0.0% or more and 5.0% or less.
[0101] BaO is a component that improves the solubility of glass raw materials. In addition, as mentioned above, since the electronegativity is lower than that of Mg and Ca, the proportion of tetracoordinated boron can be increased. On the other hand, the specific gravity of the glass increases, the brittleness decreases, and the strength of the glass may decrease, so it is preferred not to actively contain BaO. In the case of containing BaO, its content is more preferably more than 0.10%, further preferably more than 0.20%, particularly preferably more than 0.30%, extremely preferably more than 0.40%, and most preferably more than 0.50%. Thus, the solubility of the raw materials of the glass, the formability of vehicle window glass, especially windshield, etc. is improved.
[0102] In addition, the content of BaO is preferably 5.0% or less. By making the content of BaO 5.0% or less, the increase in the specific gravity of the glass can be suppressed. In addition, the increase in glass density is avoided, low brittleness is suppressed, and strength is maintained. The content of BaO is more preferably 4.0% or less, further preferably 3.0% or less, particularly preferably 2.0% or less, and most preferably 1.0% or less. That is, the content of BaO is preferably 0.0% or more and 5.0% or less.
[0103] In the present embodiment, the total of SiO2+Al2O3+B2O3, i.e., the SiO2 content, the Al2O3 content, and the B2O3 content is preferably 89% or more. When SiO2+Al2O3+B2O3 is 89% or more, in addition to reducing the specific gravity of the glass and improving the weather resistance and weathering resistance of the glass, the linear expansion coefficient of the glass can be suppressed from becoming too high, so it is suitable as a window glass for vehicles and buildings. SiO2+Al2O3+B2O3 is more preferably 90% or more, and particularly preferably 91% or more.
[0104] From the viewpoint of improving the solubility of glass raw materials and the formability of vehicle window glass, especially windshield, etc., SiO2+Al2O3+B2O3 is preferably 95% or less, more preferably 94% or less, and further preferably 93% or less. That is, SiO2+Al2O3+B2O3 is preferably 89% or more and 95% or less.
[0105] In the present embodiment, the total content of Li2O, Na2O and K2O (hereinafter sometimes referred to as R2O) is preferably 5.0% or more. By R2O being 5.0% or more, not only the proportion of tetracoordinated boron is increased, the Young's modulus becomes higher, and in addition, the viscosity of the glass is reduced, and the formability is improved, so it is preferably used as a vehicle window glass, especially as a windshield. In addition, the linear expansion coefficient can be increased within the range where the glass does not undergo thermal cracking, and the strength of the glass can be improved by performing air-cooling strengthening treatment. R2O is more preferably 6.0% or more, further preferably 6.5% or more, particularly preferably 7.0% or more, and most preferably 7.5% or more.
[0106] From the viewpoint of improving weathering resistance and suppressing excessive proportion of tetracoordinated boron, R2O is preferably 10% or less, more preferably 9.5% or less, and particularly preferably 9.0% or less. That is, R2O is preferably 5.0% or more and 10% or less.
[0107] In addition, among Li2O, Na2O and K2O, Li2O has the smallest molecular weight and contributes to the lightening of glass, and also contributes greatly to the reduction of the viscosity of glass and the improvement of Young's modulus. Therefore, among Li2O, Na2O and K2O, Li2O is preferably contained. In addition, from the viewpoint of improving weathering resistance and suppressing phase separation and devitrification by the mixed alkali effect, it is preferable to contain two or more alkali metal components.
[0108] In the present embodiment, RO represents the total content of MgO, CaO, SrO and BaO (hereinafter sometimes referred to as RO). RO is preferably 0.0% or more and 5.0% or less. If RO is 5.0% or less, the brittleness of the glass can be suppressed from decreasing, and the coordination number of boron can be controlled while maintaining the strength of the glass. RO is more preferably 4.5% or less, further preferably 4.0% or less, further preferably 3.5% or less, further preferably 3.0% or less, particularly preferably 2.5% or less, and most preferably 2.0% or less.
[0109] From the viewpoint of improving the formability of vehicle window glass, particularly windshield glass, RO is more preferably 0.20% or more, further preferably 0.50% or more, and particularly preferably 1.0% or more.
[0110] The mass ratio (%) of divalent iron converted to Fe2O3 in the total iron converted to Fe2O3 of the glass of this embodiment (hereinafter referred to as Fe-Redox) is preferably 10% or more. The value of Fe-Redox is Fe converted to Fe2O3. 2+ The ratio of the content to the total iron content converted to Fe2O3. Therefore, it is an indicator of the O2 concentration in the glass and indicates the redox state.
[0111] The glass of this embodiment can increase the Fe-Redox content having absorption in the near-infrared region by 10% or more. 2+ As a result, the transmittance in the near-infrared region is reduced, and the heat insulation can be improved. Fe-Redox is more preferably 14% or more, further preferably 16% or more, and particularly preferably 18% or more. In addition, Fe-Redox is preferably 70% or less. By making Fe-Redox 70% or less, it is possible to suppress the generation of negative divalent sulfur ions S in the glass. 2- and trivalent iron ions Fe 3+ The amber coloration produced by the combination of Fe-Redox and Fe-Redox can suppress the decrease in transmittance in the visible light region and maintain the gray glass. The Fe-Redox is more preferably 65% or less, further preferably 60% or less, and particularly preferably 55% or less. That is, the Fe-Redox is preferably 10% or more and 70% or less.
[0112] Fe-Redox can be adjusted by controlling the redox degree of the glass melt through the composition of glass raw materials, melting temperature, and use of reducing agents such as coke and ammonium chloride.
[0113] The glass of this embodiment may contain components other than the above-mentioned SiO2, Al2O3, B2O3, MgO, CaO, SrO, BaO, Li2O, Na2O, K2O, and Fe2O3 (hereinafter also referred to as "other components"). When containing these components, their total content is preferably less than 6.0%.
[0114] Other components include, for example, ZrO2, Y2O3, TiO2, CeO2, Nd2O5, GaO2, GeO2, MnO2, NiO, Cr2O3, V2O5, Er2O3, Au2O3, Ag2O, CuO, CdO, MoO3, SO3, Cl, F, SnO2, Sb2O3, etc., which may be metal ions or oxides. For various purposes (such as clarification and coloring), other components may contain a total of less than 6.0%. When the total content of other components is greater than 6.0%, SiO2+Al2O3+B2O3 is less than 89%, the specific gravity of the glass may increase, and the weather resistance and weathering resistance may decrease. In addition, the R2O content is less than 5.0%, the proportion of tri-coordinated boron may increase, the Young's modulus may decrease, and the viscosity of the glass may increase. The content of other components is more preferably 4.0% or less, further preferably 2.0% or less, further preferably 1.0% or less, particularly preferably 0.50% or less, and most preferably 0.10% or less.
[0115] In addition, Er2O3 has the same effect of making glass red as Se, but since it is a rare element, the cost is high. From the perspective of reserves, it is not suitable for mass production processes such as float method, roller method, down-draw method, etc. described later, so the content is preferably less than 0.0015%, and it is more preferably substantially free of it. In addition, in order to prevent the impact on the environment, the contents of As2O3 and PbO are preferably less than 0.0015%, and it is more preferably substantially free of it.
[0116] When the glass of the present embodiment contains NiO, the formation of NiS may cause glass fracture, so the content is preferably 0.0080% or less. The NiO content in the glass of the present embodiment is more preferably 0.0040% or less, further preferably 0.0020% or less, and particularly preferably substantially free of NiO.
[0117] The glass of the present embodiment may contain TiO2. TiO2 has absorption in the ultraviolet region, so it can reduce the ultraviolet transmittance Tuv and improve the UV cut-off performance. In the case where the glass of the present embodiment contains TiO2, its content is preferably 0.010% or more, more preferably 0.040% or more, further preferably 0.075% or more, and particularly preferably 0.15% or more. Since TiO2 has coloring on the light in the visible light region, the visible light transmittance Tv may be reduced and the color of the glass may change from gray to brown. In the case where the glass of the present embodiment contains TiO2, its content is preferably 0.80% or less, more preferably 0.50% or less, further preferably 0.40% or less, and particularly preferably 0.30% or less. That is, the content of TiO2 is preferably 0.0% or more and 0.80% or less.
[0118] The glass of the present embodiment may contain CeO2. Since CeO2 has absorption in the ultraviolet region, it can reduce the ultraviolet transmittance Tuv and improve the UV cut-off performance. In the case where the glass of the present embodiment contains CeO2, its content is preferably 0.010% or more, more preferably 0.020% or more, further preferably 0.040% or more, and particularly preferably 0.070% or more. CeO2 produces sunlight by absorbing light in the ultraviolet region, and the transmittance in the visible light region is reduced, and the color of the glass may not be gray. In the case where the glass of the present embodiment contains CeO2, its content is preferably 0.25% or less, more preferably 0.18% or less, further preferably 0.14% or less, and particularly preferably 0.10% or less. That is, the content of CeO2 is preferably 0.0% or more and 0.25% or less.
[0119] The glass of this embodiment may contain Cr2O3. Cr2O3 acts as an oxidant and can control the Fe 2+ In the case where the glass of the present embodiment contains Cr2O3, its content is preferably 0.0020% or more, and more preferably 0.0040% or more. Cr2O3 has coloring on light in the visible light region, so the visible light transmittance may be reduced. In the case where the glass of the present embodiment contains Cr2O3, its content is preferably 0.020% or less, more preferably 0.016% or less, further preferably 0.012% or less, and particularly preferably 0.0080% or less. That is, the content of Cr2O3 is preferably 0.0% or more and 0.020% or less.
[0120] The glass of the present embodiment may contain SnO2. SnO2 acts as a reducing agent and can control the amount of FeO. When the glass of the present embodiment contains SnO2, its content is preferably 0.010% or more, more preferably 0.040% or more, further preferably 0.060% or more, and particularly preferably 0.080% or more. On the other hand, in order to suppress defects caused by SnO2 when manufacturing glass, the content of SnO2 in the glass of the present embodiment is preferably 0.40% or less, more preferably 0.30% or less, further preferably 0.20% or less, and particularly preferably 0.15% or less. That is, the content of SnO2 is preferably 0.0% or more and 0.40% or less.
[0121] The glass of the present embodiment may contain SO3. SO3 acts as a clarifier, so the bubble quality of the glass can be improved. In the case where the glass of the present embodiment contains SO3, its content is preferably 0.0010% or more, more preferably 0.0040% or more, further preferably 0.0070% or more, and particularly preferably 0.015% or more. SO3 may produce an amber color when Fe-Redox is high, and the glass may turn brown. In the case where the glass of the present embodiment contains SO3, its content is preferably 0.070% or less, more preferably 0.060% or less, further preferably 0.050% or less, and particularly preferably 0.040% or less. That is, the content of SO3 is preferably 0.0% or more and 0.070% or less.
[0122] The glass of the present embodiment may contain Cl. Cl acts as a clarifier, so the bubble quality of the glass can be improved. In the case where the glass of the present embodiment contains Cl, its content is preferably 0.080% or more, more preferably 0.15% or more, further preferably 0.20% or more, particularly preferably 0.30% or more, and most preferably 0.40% or more. When the Cl content is too much, the Cl2 gas volatilized from the molten glass may corrode the surrounding components. In the case where the glass of the present embodiment contains Cl, its content is preferably 1.5% or less, more preferably 1.2% or less, further preferably 1.0% or less, and particularly preferably 0.80% or less. That is, the Cl content is preferably 0.0% or more and 1.5% or less.
[0123] <Other features>
[0124] (Visible light transmittance: Tv)
[0125] When the thickness is converted to 2.0 mm, the glass of the present embodiment preferably has a visible light transmittance Tv calculated by measuring the transmittance using a spectrophotometer using a D65 light source according to the provisions of ISO-9050:2003, which is preferably 75% or more. With Tv being 75% or more, it is suitable for use as a windshield or door glass for a vehicle due to excellent transparency. Tv is more preferably 78% or more, and further preferably 80% or more. The upper limit of Tv is not particularly limited, and is, for example, 91% or less. That is, Tv is, for example, 75% or more and 91% or less.
[0126] In addition, the glass of the present embodiment can adjust the absorption of light in the visible light region by adjusting the ratio of tricoordinate boron to tetracoordinate boron as described above, so the glass of the present embodiment can also be used as a rear window glass for a vehicle. When the glass of the present embodiment is used as a rear window glass for a vehicle, the Tv of the glass is preferably less than 75%, more preferably less than 72%, and further preferably less than 70%.
[0127] The glass of this embodiment preferably has a low solar transmittance Te and a high visible light transmittance Tv. That is, Tv / Te is preferably 1.05 or more. When Tv / Te is 1.05 or more, the glass exhibits excellent transparency and heat insulation, and is more suitable as a window glass for vehicles and buildings. The upper limit of Tv / Te is not particularly limited, for example, it is 1.30 or less. That is, Tv / Te is, for example, 1.05 or more and 1.30 or less.
[0128] (Ultraviolet transmittance: Tuv)
[0129] The glass of this embodiment preferably has low ultraviolet transmittance. When the thickness is converted to 2.0 mm, the ultraviolet transmittance Tuv defined by ISO-9050:2003 is preferably 65% or less. Tuv is more preferably 60% or less, further preferably 55% or less, particularly preferably 50% or less, and most preferably 45% or less. In addition, Tuv is, for example, 5% or more. That is, Tuv is, for example, 5% or more and 65% or less.
[0130] (Young's modulus)
[0131] The Young's modulus of the glass of this embodiment is preferably 65 GPa or more, more preferably 68 GPa or more, further preferably 70 GPa or more, and particularly preferably 72 GPa or more. When the Young's modulus is within the above range, the glass has high rigidity, which is more preferred for vehicle window glass and the like.
[0132] On the other hand, when Young's modulus is too high, glass is difficult to deform, and therefore may not be able to absorb the energy during the collision of flying stones and glass breaks. Therefore, Young's modulus is below 80GPa, more preferably below 78GPa, further preferably below 75GPa. That is, Young's modulus is preferably above 65GPa and below 80GPa.
[0133] (T 11 )
[0134] In the glass of this embodiment, the glass viscosity reaches 10 11 [dPa·s] at temperature T 11 It is preferably 640°C or lower. 11 The temperature is 640°C or lower, and bending forming at low temperature is possible.
[0135] As a T 11 The method of reducing the temperature to 640°C or below includes, for example, increasing the contents of B2O3, R2O, and RO in the glass components and reducing the content of Al2O3; and also including Li2O in R2O. In the glass of this embodiment, T 11 It is more preferably 620°C or lower, further preferably 615°C or lower, further preferably 610°C or lower, particularly preferably 605°C or lower, and most preferably 600°C or lower.
[0136] In addition, from the perspective of the calcination temperature of the black ceramic printed on the windshield, T 11 It is preferably 560°C or higher, more preferably 570°C or higher, further preferably 575°C or higher, and particularly preferably 580°C or higher. 11 It is preferably 560°C or higher and 640°C or lower.
[0137] (T 12 )
[0138] In the glass of this embodiment, the glass viscosity reaches 10 12 [dPa·s] at temperature T 12 It is preferably 600°C or lower. 12 The temperature is 600°C or lower, and bending forming at low temperature is possible.
[0139] As a T 12 The method of reducing the temperature to below 600°C includes, for example, increasing the contents of B2O3, R2O, and RO in the glass components and reducing the content of Al2O3; and also including Li2O in R2O. In the glass of this embodiment, T 12 The temperature is more preferably 595°C or lower, further preferably 590°C or lower, further preferably 585°C or lower, particularly preferably 580°C or lower, and most preferably 575°C or lower.
[0140] In addition, from the perspective of the firing temperature of the black ceramic printed on the windshield, T 12 It is preferably 540°C or higher, more preferably 545°C or higher, further preferably 550°C or higher, particularly preferably 555°C or higher, and most preferably 560°C or higher. 12 It is preferably 540°C or higher and 600°C or lower.
[0141] (Average linear expansion coefficient)
[0142] The average linear expansion coefficient of the glass of the present embodiment in the range of 50°C to 350°C is preferably 40×10 -7 / °C or more. The glass of this embodiment has an average linear expansion coefficient of 40×10 -7 / ℃ or above, in addition to being easy to be treated by air cooling and strengthening, it can also reduce the difference in linear expansion coefficient with black ceramics and inhibit cracks in black ceramics. In order to make the average linear expansion coefficient within the above range, the method of increasing the content of B2O3, R2O and RO in the glass component and reducing the content of Al2O3 can be cited.
[0143] The average linear expansion coefficient of the glass of the present embodiment in the range of 50°C to 350°C is more preferably 45×10 -7 / ℃ or more, more preferably 47×10 -7 / ℃ or more, particularly preferably 50×10 -7 / ℃ or above, the most preferred is 52×10 -7 / ℃ or above.
[0144] On the other hand, when the average linear expansion coefficient of the glass of the present embodiment is too large, thermal stress caused by the temperature distribution of the glass is easily generated in the glass forming process, slow cooling process or windshield forming process, and thermal cracking of the glass may occur. In addition, when the average linear expansion coefficient of the glass of the present embodiment becomes too large, cracks caused by thermal shock may occur when it is used as vehicle window glass or building window glass. The average linear expansion coefficient of the glass of the present embodiment in the range of 50°C to 350°C can be 70×10 -7 / ℃ or less, preferably 65×10 -7 / °C or less, more preferably 63×10 -7 / °C or less, more preferably 60×10 -7 / °C or less. That is, the average linear expansion coefficient in the range of 50°C to 350°C is preferably 40×10 -7 / ℃ and above 70×10 -7 / ℃ below.
[0145] (proportion)
[0146] The specific gravity of the glass of the present embodiment is preferably 2.40 or less.
[0147] The specific gravity of soda-lime glass widely used as window glass for vehicles and buildings is about 2.51, but since the glass of this embodiment is an alkali borosilicate glass with a smaller specific gravity than soda-lime glass, it is light in weight and can be more suitable for use as window glass for vehicles and buildings from the perspective of fuel efficiency and power consumption rate. The specific gravity of the glass of this embodiment is more preferably 2.38 or less, further preferably 2.36 or less, and particularly preferably 2.34 or less. In addition, from the perspective of improving the sound insulation in the car, the specific gravity of the glass of this embodiment is preferably 2.25 or more, and further preferably 2.27 or more. That is, the specific gravity of the glass is preferably 2.25 or more and 2.40 or less.
[0148] In the glass of this embodiment, T 2.5 Preferably, it is 1600°C or lower. In the glass of this embodiment, T4 is preferably 1200°C or lower, and T4-T L It is preferably -50°C or higher. It should be noted that in this specification, T 2.5 Indicates that the glass viscosity reaches 10 2.5 dPa·s, T4 means the temperature at which the glass viscosity reaches 10 4 Temperature at dPa·s, T L Indicates the liquidus temperature of glass.
[0149] When the glass of this embodiment has a T 2.5 When T4 is higher than these specified temperatures, it is difficult to manufacture large glass by float process, roll process, down-draw process, etc. In the glass of this embodiment, T 2.5 It is more preferably 1550° C. or lower, further preferably 1500° C. or lower, and particularly preferably 1480° C. or lower. In the glass of this embodiment, T4 is more preferably 1180° C. or lower, further preferably 1150° C. or lower, and particularly preferably 1125° C. or lower.
[0150] In addition, the T of the glass of this embodiment is 2.5 There is no particular limit on the lower limit of T4. In order to maintain weather resistance and weathering resistance, typically, T 2.5 The glass of this embodiment has a temperature T of 1300°C or higher and a temperature T4 of 1000°C or higher. 2.5 It is preferably 1350° C. or higher, and more preferably 1380° C. or higher. T4 of the glass of this embodiment is preferably 1020° C. or higher, and more preferably 1050° C. or higher. That is, T 2.5 The temperature is 1300°C or higher and preferably 1600°C or lower, and T4 is preferably 1000°C or higher and 1200°C or lower.
[0151] In order to be able to manufacture by the float process, the glass of this embodiment has a T4-T L Preferably, the difference is -50°C or more. If the difference is -50°C or more, devitrification in the glass during glass forming can be suppressed, the mechanical properties of the glass are improved, and the transparency is improved, thereby obtaining glass of excellent quality. L It is more preferably -25°C or higher, further preferably 0°C or higher, and particularly preferably 20°C or higher.
[0152] In addition, the glass of this embodiment is preferably T g It is 460°C or higher and 580°C or lower. g represents the glass transition temperature. If T g Within this specified temperature range, the glass can be bent within the range of normal manufacturing conditions. g When the temperature is lower than 460°C, there is no problem with formability, but the alkali content or alkaline earth content becomes too high, which may cause problems such as excessive thermal expansion of the glass or reduced weather resistance and weathering resistance. g If the temperature is lower than 460° C., the glass may lose clarity in the forming temperature range and may not be formed.
[0153] The glass of this embodiment has a T g It is more preferably 480° C. or higher, further preferably 490° C. or higher, and particularly preferably 500° C. or higher. On the other hand, from the viewpoint of facilitating the manufacturing process during the glass bending process, the T of the glass of the present embodiment is g The temperature is more preferably 570°C or lower, further preferably 565°C or lower, and particularly preferably 560°C or lower.
[0154] In the alkali borosilicate glass of this embodiment, when water exists in the glass, the T 11 and T 12 The effect of bending the glass becomes easier. Therefore, the alkali borosilicate glass of this embodiment preferably contains a certain amount of water. The water content in the glass can usually be expressed by a value such as β-OH value, and the β-OH value is preferably 0.050 mm -1 More preferably 0.10 mm -1 More preferably, 0.15 mm -1 Above, particularly preferably 0.20 mm -1 The β-OH is obtained by the following formula from the transmittance of glass measured using FT-IR (Fourier transform infrared spectrophotometer).
[0155] β-OH=(1 / X)log 10 (T A / T B )[mm -1 ]
[0156] X: Thickness of sample [mm]
[0157] T A :Reference wave number 4000cm -1 Transmittance under [%]
[0158] T B :Hydroxy absorption wave number 3600cm -1 Minimum transmittance near [%]
[0159] On the other hand, when the amount of water in the glass is too much, the network structure of the glass may be affected, thereby deteriorating the anti-flying stone property. Therefore, the β-OH value of the alkali borosilicate glass of the present embodiment is preferably 0.70 mm -1 Below, more preferably 0.60 mm -1 Below, more preferably 0.50 mm -1 Below, particularly preferably 0.40 mm -1 That is, the β-OH value is preferably 0.050 mm -1 Above and 0.70mm -1 the following.
[0160] When the thickness is converted to 2.00 mm, the L value of the glass of this embodiment obtained by using a D65 light source as defined in JIS Z 8781-4:2003 is * It is preferably 84.0 or more, more preferably 86.0 or more, further preferably 88.0 or more, and further preferably 90.0 or more. * The upper limit of L is not particularly limited, but is 100.0 or less. * It is preferably 84.0 or more and 100.0 or less.
[0161] When the thickness is converted to 2.00 mm, the glass of the present embodiment obtained using a D65 light source has a value defined in JIS Z 8781-4:2003. * It is preferably -5.0 or more, more preferably -3.0 or more, and even more preferably -2.0 or more. * It is preferably 2.0 or less, more preferably 1.0 or less, and still more preferably 0.0 or less. * It is preferably -5.0 or more and 2.0 or less.
[0162] In addition, when the thickness is converted to 2.00 mm, using D65 light source, b defined by JIS Z 8781-4:2003* It is preferably -5.0 or more, more preferably -3.0 or more, and even more preferably -1.0 or more. * It is preferably 5.0 or less, more preferably 3.0 or less, further preferably 2.0 or less, and particularly preferably 1.5 or less. * It is preferably -5.0 or more and 5.0 or less.
[0163] The glass of this embodiment is L * 、a * and b * When the content is within the above range, the glass has excellent design properties and can be suitably used as window glass for vehicles or buildings.
[0164] In addition, the glass of this embodiment is composed of c * ={(a * ) 2 +(b * ) 2} 1 / 2 The obtained c * It is preferably 3.5 or less, more preferably 3.0 or less, further preferably 2.5 or less, and particularly preferably 2.0 or less. * The smaller the value, the lower the saturation, and the glass becomes dark gray. * The lower limit of is not particularly limited, but is usually greater than 0.0. * It is preferably 0.0 or more and 3.5 or less.
[0165] The glass of this embodiment is preferably a float glass formed by, for example, a known float process, in which a molten glass blank is floated on a molten metal such as tin, and in addition to being able to form a glass with uniform thickness and width through strict temperature operation, a large area of glass can also be obtained.
[0166] Alternatively, the glass may be formed by a known rolling method or down-drawing method, or the surface may be polished to make the glass uniform in thickness. Here, the down-drawing method is roughly divided into a flow hole down-drawing method and an overflow down-drawing method (fusion method), but both methods are methods of continuously flowing molten glass from a forming body to form a glass ribbon in a ribbon-shaped plate.
[0167] The shape of the glass of this embodiment is not particularly limited, but the area of the main surface is preferably 250000 mm 2 More than 450000mm 2 More than, more preferably 900000mm 2When the area of the glass is within the above range, it can be used for various types of vehicles. In addition, when the area of the glass is too large, the handling of the glass becomes difficult, the temperature distribution during heating becomes uneven, the dimensional accuracy after bending becomes poor, and the difficulty of bending becomes higher. Therefore, the area of the main surface of the glass in this embodiment is preferably 4000000mm 2 Below, more preferably 3500000mm 2 Below, more preferably 3000000mm 2 That is, the glass of this embodiment preferably has a main surface area of 250000 mm 2 Above and 4000000mm 2 the following.
[0168] In addition, in order to improve rigidity, improve the strength when flying stones, vehicle keys, etc. contact with glass, the preferred thickness of the glass of the present embodiment is more than 0.50mm. The thickness of glass is more preferably more than 1.00mm, more preferably more than 1.50mm, particularly preferably more than 2.00mm, and most preferably more than 2.50mm. In addition, from the viewpoint of suppressing the increase of fuel efficiency and power consumption rate accompanying the weight increase of glass, the thickness of the glass of the present embodiment is preferably less than 4.00mm, more preferably less than 3.80mm, and more preferably less than 3.50mm. That is, the thickness of glass is preferably more than 0.50mm and less than 4.00mm.
[0169] The glass of this embodiment may be glass subjected to a strengthening treatment such as air cooling strengthening or chemical strengthening. By performing the above treatment, the strength of the glass can be increased.
[0170] Here, air-cooling strengthening refers to a process of forming a compressive stress layer on the glass surface by heat strengthening treatment. Specifically, the uniformly heated glass plate is rapidly cooled from a temperature near the softening point, and compressive stress is formed on the glass surface due to the temperature difference between the glass surface and the inside of the glass. Compressive stress is uniformly generated on the entire surface of the glass, and a compressive stress layer of uniform depth is formed on the entire surface of the glass. Compared with chemical strengthening treatment, heat strengthening treatment is suitable for strengthening thick glass plates.
[0171] In addition, chemical strengthening refers to the process of exchanging alkali metal ions with small ionic radius (typically, Li ions or Na ions) on the surface of the glass with alkali metal ions with larger ionic radius (typically, Na ions or K ions) by ion exchange at a temperature below the glass transition temperature, thereby forming a compressive stress layer on the surface of the glass. The chemical strengthening treatment method can be implemented by a known method, such as an ion exchange method. In the ion exchange method, the glass plate is immersed in a treatment solution (such as potassium nitrate molten salt), and the ions with small ionic radius (such as Na ions) contained in the glass are exchanged for ions with large ionic radius (such as K ions), thereby generating compressive stress on the surface of the glass.
[0172] The magnitude of the compressive stress on the glass plate surface (hereinafter also referred to as surface compressive stress CS) and the depth DOL of the compressive stress layer formed on the glass plate surface can be adjusted by the glass composition, chemical strengthening treatment time and chemical strengthening treatment temperature, respectively.
[0173] [Bent glass]
[0174] The curved glass of this embodiment includes the alkali borosilicate glass. That is, the alkali borosilicate glass is bent and formed. The curved glass of this embodiment may be a curved glass obtained by forming the alkali borosilicate glass in a flat plate shape into a curved shape by gravity forming or press forming.
[0175] The curved glass of this embodiment is glass curved with a predetermined curvature, and may be one-way curved glass curved only in one direction, or may be two-way curved glass curved in both directions.
[0176] The minimum value of the radius of curvature of the curved glass of the present embodiment is preferably greater than or equal to 500 mm and less than or equal to 100000 mm. The radius of curvature of the curved glass is calculated by shape simulation using a laser displacement meter (Dyvoce manufactured by Kamijutsu Seiki Co., Ltd.) based on the original warpage of the sample obtained by self-weight deflection correction using a double-sided differential mode, and the radius of curvature is obtained from the shape obtained by the simulation.
[0177] [Method for manufacturing bent glass]
[0178] In the method for producing curved glass according to the present embodiment, the curved glass is formed by heating and bending the alkali borosilicate glass.
[0179] As a method for forming curved glass, there is a method of bending the heated glass by pressing it from above with a pressing mechanism in a state where the heated glass is placed on a forming die.
[0180] Another method is to place a flat plate of glass on a forming mold having a curved forming surface corresponding to a desired curved surface, carry the forming mold into a heating furnace in this state, and heat the glass to a temperature near the softening point of the glass in the heating furnace. According to this forming method, the glass bends along the curved forming surface of the forming mold due to its own weight as it softens, thereby manufacturing glass having a desired curved surface.
[0181] In this embodiment, from the viewpoint of improving productivity and surface accuracy after forming, it is preferred to use the above-mentioned pressing mechanism for bending forming. The bending forming method using the above-mentioned pressing mechanism is not particularly limited, and for example, the method described in International Publication No. 2016 / 093031 etc. can be appropriately adopted. The bending forming method using the above-mentioned pressing mechanism is described illustratively below.
[0182] First, the alkali borosilicate glass of the present embodiment is conveyed to a press area by a conveyor belt, etc. Next, in the press area, the alkali borosilicate glass is heated to a temperature at which it can be bent and formed, and is softened.
[0183] Here, the bending temperature is, for example, a temperature at which the glass viscosity reaches 10 11 [dPa·s] at temperature T 11 It should be noted that the heating can be performed by using a heater or the like in a heating furnace during the process of being transported to the pressing area by using a conveyor or the like.
[0184] In addition, as the heating temperature (≥T 11 ) conditions, the bending forming time can be set to, for example, more than 1 second.
[0185] A lower pressing mold (female mold) and an upper pressing mold (male mold) are arranged at predetermined positions in the pressing area, and the upper surface shape of the female mold and the lower surface shape of the male mold correspond to the curved shape of the alkali borosilicate glass to be bent in the conveying direction and the orthogonal direction. The female mold can be raised and lowered between a standby position below the conveyor and a pressing position above the conveyor. After the glass is transferred from the conveyor, the female mold is raised from a predetermined raising position to a pressing position above the conveyor while the glass is loaded, thereby pressing and forming the alkali borosilicate glass.
[0186] Next, the press-formed alkali borosilicate glass is conveyed to a cooling zone by a shuttle conveyor. In the cooling zone, the alkali borosilicate glass is cooled by blowing cooling air or the like to the alkali borosilicate glass.
[0187] It should be noted that, in the above, the bending of the alkali borosilicate glass of the present embodiment has been described, but the bending may be performed in the state of laminated glass described later.
[0188] [Laminated glass]
[0189] The laminated glass of the present embodiment includes a first glass plate, a second glass plate, and an intermediate film interposed between the first glass plate and the second glass plate, and the first glass plate is the above-mentioned alkali borosilicate glass or the above-mentioned curved glass.
[0190] Figure 4 1 is a diagram showing an example of a laminated glass 10 according to the present embodiment. The laminated glass 10 includes a first glass plate 11, a second glass plate 12, and an intermediate film 13 sandwiched between the first glass plate 11 and the second glass plate 12. It should be noted that the laminated glass 10 according to the present embodiment is not limited to Figure 4 The present invention can be modified in the following manner without departing from the scope of the present invention. Figure 4 As shown in FIG. 1 , the intermediate film 13 may be formed of one layer or may be formed of two or more layers. In addition, the laminated glass 10 of the present embodiment may have three or more glass plates, in which case an organic resin or the like may be sandwiched between adjacent glass plates. Hereinafter, the laminated glass 10 of the present embodiment will be described as having a structure in which the glass plates include only two glass plates, the first glass plate 11 and the second glass plate 12, and the intermediate film 13 is sandwiched therebetween.
[0191] In the laminated glass of the present embodiment, from the viewpoint of bending formability, the second glass plate 12 is preferably the above-mentioned alkali borosilicate glass or the above-mentioned curved glass. When the first glass plate 11 and the second glass plate 12 are the above-mentioned alkali borosilicate glass or the above-mentioned curved glass, the first glass plate 11 and the second glass plate 12 may use glass plates of the same composition or glass plates of different compositions.
[0192] When the second glass plate 12 is not the above-mentioned alkali borosilicate glass, the type of the glass plate is not particularly limited, and a conventionally known glass plate used in vehicle window glass, etc. can be used. Specifically, alkali aluminosilicate glass, alkali aluminoborosilicate glass, and soda-lime glass can be cited. These glass plates may be colored to the extent that the transparency is not impaired, or may not be colored.
[0193] In the laminated glass of the present embodiment, the second glass plate 12 may be an alkali aluminosilicate glass containing 1.0% or more of Al2O3 or an alkali aluminoborosilicate glass containing 1.0% or more of Al2O3 and 1.0% or more of B2O3. By making the second glass plate 12 into the above-mentioned alkali aluminosilicate glass or alkali aluminoborosilicate glass, chemical strengthening can be performed as described later, and high strength can be achieved.
[0194] From the viewpoint of improving weather resistance, weathering resistance and chemical strengthening characteristics, the Al2O3 content of the above-mentioned alkali aluminosilicate glass and alkali aluminoborosilicate glass is more preferably 5.0% or more, further preferably 8.0% or more, and particularly preferably 10% or more. In addition, in order to reduce the viscosity of the glass and facilitate manufacturing, the Al2O3 content is preferably 18% or less, and more preferably 15% or less.
[0195] From the viewpoint of chemical strengthening, the content of R2O in the alkali aluminosilicate glass and the alkali aluminoborosilicate glass is preferably 10% or more, more preferably 12% or more, and further preferably 13% or more. In addition, from the viewpoint of improving weathering resistance, the content of R2O is preferably 22% or less, more preferably 20% or less, and further preferably 18% or less.
[0196] In order to improve the strength when flying stones, vehicle keys, etc. come into contact with the glass, the B2O3 content of the above-mentioned alkali aluminoborosilicate glass is preferably 2.0% or more, more preferably 3.0% or more, and further preferably 4.0% or more. In addition, in the alkali aluminoborosilicate glass, from the viewpoint of improving chemical durability and weather resistance, the B2O3 content is preferably 9.0% or less, more preferably 8.0% or less, and further preferably 7.0% or less.
[0197] As the above-mentioned alkali-aluminosilicate glass, specifically, the glass of the following composition can be exemplified. Each component is calculated by molar percentage based on oxide. 61%≤SiO2≤77%, 1.0%≤Al2O3≤20%, 0.0%≤MgO≤15%, 0.0%≤CaO≤10%, 0.0%≤SrO≤1.0%, 0.0%≤BaO≤1.0%, 0.0%≤Li2O≤15%, 2.0%≤Na2O≤15%, 0.0%≤K2O≤6.0%, 0.0%≤ZrO2≤4.0%, 0.0%≤TiO2≤1.0%, 0.0%≤Y2O3≤2.0%, 10%≤R2O≤25%, 0.0%≤RO≤20%, (R2O represents the total content of Li2O, Na2O and K2O, and RO represents the total content of MgO, CaO, SrO and BaO.).
[0198] Specific examples of the alkali-aluminoborosilicate glass include glasses having the following compositions: The molar percentages of the components are expressed as oxides. 61%≤SiO2≤77%, 1.0%≤Al2O3≤20%, 1.0%≤B2O3≤10%, 0.0%≤MgO≤15%, 0.0%≤CaO≤10%, 0.0%≤SrO≤1.0%, 0.0%≤BaO≤1.0%, 0.0%≤Li2O≤15%, 2.0%≤Na2O≤15%, 0.0%≤K2O≤6.0%, 0.0%≤ZrO2≤4.0%, 0.0%≤TiO2≤1.0%, 0.0%≤Y2O3≤2.0%, 10%≤R2O≤25%, 0.0%≤RO≤20%, (R2O represents the total content of Li2O, Na2O and K2O, RO represents the total content of MgO, CaO, SrO and BaO).
[0199] In the laminated glass of the present embodiment, the second glass plate 12 may be soda-lime glass. The soda-lime glass may be soda-lime glass containing less than 1.0% of Al2O3. Specifically, the following glass compositions may be exemplified. The molar percentage of each component is based on oxide.
[0200] 60%≤SiO2≤75%, 0.0%≤Al2O3<1.0%, 2.0%≤MgO≤11%, 2.0%≤CaO≤10%, 0.0%≤SrO≤3.0%, 0.0%≤BaO≤3.0%, 10%≤Na2O≤18%, 0.0%≤K2O≤8.0%, 0.0%≤ZrO2≤4.0%, 0.0010%≤Fe2O3≤5.0%.
[0201] In the laminated glass of the present embodiment, the second glass plate 12 may be soda-lime glass having the following composition: Each component is expressed in molar percentage based on oxides.
[0202] 60%≤SiO2≤75%, 0.0%≤Al2O3≤3.5%, 2.0%≤MgO≤11%, 2.0%≤CaO≤10%, 0.0%≤SrO≤3.0%, 0.0%≤BaO≤3.0%, 10%≤Na2O≤18%, 0.0%≤K2O≤8.0%, 0.0%≤ZrO2≤4.0%, 0.0010%≤Fe2O3≤5.0%.
[0203] The first glass plate 11 and the second glass plate 12 preferably have the same thickness. When the first glass plate 11 and the second glass plate 12 have the same thickness, the dimensional accuracy during bending is improved. In addition, in the present embodiment, the thickness of the first glass plate 11 is more preferably greater than the thickness of the second glass plate 12. It should be noted that the thickness of the first glass plate 11 and the thickness of the second glass plate 12 may also be different.
[0204] The thickness of the first glass plate 11 is preferably 2.00 mm or more. When the thickness of the first glass plate 11 is 2.00 mm or more, the sound insulation and the flying stone resistance are improved. The thickness of the first glass plate 11 is more preferably 2.25 mm or more, further preferably 2.50 mm or more, particularly preferably 2.75 mm or more, and most preferably 3.00 mm or more. In addition, the thickness of the first glass plate 11 is preferably 5.00 mm or less. When the thickness of the first glass plate 11 is 5.00 mm or less, the weight of the laminated glass 10 will not become too large, which is preferred from the perspective of improving the power consumption rate and fuel efficiency when used in a vehicle. The thickness of the first glass plate 11 is more preferably 4.75 mm or less, further preferably 4.50 mm or less, particularly preferably 4.25 mm or less, and most preferably 4.00 mm or less. That is, the thickness of the first glass plate 11 is preferably 2.00 mm or more and 5.00 mm or less.
[0205] The thickness of the second glass plate 12 is preferably less than 2.00 mm. When the thickness of the second glass plate 12 is less than 2.00 mm, even if the thickness of the first glass plate 11 is increased, the weight of the laminated glass 10 will not be too large, which is preferable from the viewpoint of improving the power consumption rate and fuel efficiency when used in a vehicle. The thickness of the second glass plate 12 is more preferably 1.80 mm or less, further preferably 1.50 mm or less, particularly preferably 1.30 mm or less, and most preferably 1.10 mm or less. In addition, the thickness of the second glass plate 12 is preferably 0.500 mm or more. In addition, when the thickness of the second glass plate 12 is 0.500 mm or more, the strength of the vehicle key and the like when in contact with the glass in the vehicle is improved. The thickness of the second glass plate 12 is more preferably 0.700 mm or more, further preferably 0.800 mm or more, and particularly preferably 0.900 mm or more. That is, the thickness of the second glass plate 12 is preferably greater than or equal to 0.500 mm and less than 2.00 mm.
[0206] In the laminated glass 10 of the present embodiment, the total thickness of the first glass plate 11, the second glass plate 12 and the intermediate film 13 is preferably 2.80 mm or more. With the total thickness being 2.80 mm or more, sufficient strength can be obtained. The total thickness is more preferably 3.00 mm or more, further preferably 3.50 mm or more, further preferably 4.00 mm or more, particularly preferably 4.50 mm or more, and most preferably 4.70 mm or more. In addition, from the viewpoint of lightweight, the total thickness may be 6.00 mm or less, preferably 5.80 mm or less, more preferably 5.60 mm or less, and further preferably 5.40 mm or less. That is, the total thickness is preferably 2.80 mm or more and 6.00 mm or less.
[0207] It should be noted that, in the laminated glass 10 of the present embodiment, the thickness of the first glass plate 11 and the second glass plate 12 can be constant over the entire surface, or can be configured as a wedge shape in which the thickness of one or both of the first glass plate 11 and the second glass plate 12 gradually decreases, and can be changed according to position as needed.
[0208] One of the first glass plate 11 and the second glass plate 12 may be a chemically strengthened glass that has been strengthened to increase its strength. The method of chemical strengthening treatment is the same as the chemical strengthening treatment of the above-mentioned alkali borosilicate glass. Chemically strengthened glass includes, for example, glass obtained by chemically strengthening the above-mentioned alkali aluminosilicate glass and the above-mentioned alkali aluminoborosilicate glass.
[0209] The shape of the first glass plate 11 and the second glass plate 12 may be a flat plate or a curved shape having a curvature on the entire surface or a portion thereof. When the first glass plate 11 and the second glass plate 12 are curved, they may be a unidirectional curved shape that is curved only in one direction of the up-down direction or the left-right direction, or a bidirectional curved shape that is curved in both the up-down direction or the left-right direction. When the first glass plate 11 and the second glass plate 12 are bidirectionally curved, the radii of curvature in the up-down direction and the left-right direction may be the same or different. When the first glass plate 11 and the second glass plate 12 are curved, the radii of curvature in the up-down direction and / or the left-right direction are preferably greater than 1000 mm. The shape of the main surface of the first glass plate 11 and the second glass plate 12 is a shape that is suitable for the window opening of the vehicle on which they are mounted.
[0210] The interlayer film 13 of this embodiment is sandwiched between the first glass plate 11 and the second glass plate 12. The laminated glass 10 of this embodiment has the interlayer film 13, which can firmly bond the first glass plate 11 and the second glass plate 12 and can mitigate the impact force when the scattered pieces collide with the glass plates.
[0211] As the intermediate film 13 , various organic resins that are conventionally generally used in laminated glass for use as laminated glass for vehicles can be used. As organic resins, for example, polyethylene (PE), ethylene-vinyl acetate copolymer (EVA), polypropylene (PP), polystyrene (PS), methacrylic resin (PMA), polyvinyl chloride (PVC), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), cellulose acetate (CA), diallyl phthalate resin (DAP), urea-formaldehyde resin (UP), melamine resin (MF), unsaturated polyester (UP), polyvinyl butyral (PVB), polyvinyl formal (PVF), polyvinyl alcohol (PVAL), vinyl acetate resin (PVAc), ionomer (IO), polymethylpentene (TPX), polyvinylidene chloride (PVDC), polysulfone (PSF), polyvinylidene fluoride (PVDF), methacrylic acid-styrene copolymer resin (MS), polyarylate (PAR), polyaryl sulfone (PASF), polybutadiene (BR), polyether sulfone (PESF) or polyether ether ketone (PEEK) can be used. Among them, EVA and PVB are preferred from the viewpoint of transparency and strong adhesion, and PVB is particularly preferred because it can impart sound insulation properties.
[0212] From the perspective of mitigating impact force and sound insulation, the thickness of the intermediate film 13 is preferably 0.300 mm or more, more preferably 0.500 mm or more, and further preferably 0.700 mm or more. In addition, from the perspective of suppressing the reduction of visible light transmittance, the thickness of the intermediate film 13 is preferably 1.00 mm or less, more preferably 0.900 mm or less, and further preferably 0.800 mm or less. In addition, the thickness of the intermediate film 13 is preferably in the range of 0.300 mm to 1.00 mm, and more preferably in the range of 0.700 mm to 0.800 mm.
[0213] The thickness of the intermediate film 13 may be constant over the entire surface, or may be changed at different locations as required.
[0214] It should be noted that, when the difference in linear expansion coefficient between the intermediate film 13 and the first glass plate 11 or the second glass plate 12 is large, when the laminated glass 10 is manufactured through the heating process described later, cracks and warping may occur in the laminated glass 10, causing poor appearance. Therefore, it is preferable that the difference in linear expansion coefficient between the intermediate film 13 and the first glass plate 11 or the second glass plate 12 is as small as possible. The difference in linear expansion coefficient between the intermediate film 13 and the first glass plate 11 or the second glass plate 12 can be expressed as the difference between the average linear expansion coefficients within a predetermined temperature range.
[0215] In particular, since the glass transition temperature of the resin constituting the intermediate film 13 is low, a predetermined average linear expansion coefficient difference can be set within a temperature range below the glass transition temperature of the resin material. It should be noted that the difference in linear expansion coefficient between the first glass plate 11 or the second glass plate 12 and the resin material can be set based on a predetermined temperature below the glass transition temperature of the resin material.
[0216] In addition, an adhesive layer containing an adhesive may be used for the intermediate film 13 . The adhesive is not particularly limited, and for example, an acrylic adhesive, a silicone adhesive, or the like may be used.
[0217] When the intermediate film 13 is an adhesive layer, since a heating step is not required in the bonding process of the first glass plate 11 and the second glass plate 12 , the possibility of the above-mentioned cracks and warping is small.
[0218] [Other layers]
[0219] The laminated glass 10 of this embodiment may have layers other than the first glass plate 11, the second glass plate 12 and the intermediate film 13 (hereinafter also referred to as "other layers") within the range that does not impair the effects of the present invention. For example, it may have a coating layer that imparts a water-repellent function, a hydrophilic function, an anti-fog function, an infrared reflective film, etc.
[0220] There is no particular limitation on the position of the other layers, and they may be provided on the surface of the laminated glass 10, or may be provided between the first glass plate 11, the second glass plate 12, or the intermediate film 13. In addition, in order to conceal the upper portion mounted on the frame, etc., wiring conductors, etc., the laminated glass 10 of this embodiment may have a black ceramic layer provided in a strip shape on part or all of the peripheral portion.
[0221] The manufacturing method of the laminated glass 10 of the present embodiment can be manufactured by the same method as the conventionally known laminated glass. For example, by sequentially laminating the first glass plate 11, the intermediate film 13, and the second glass plate 12, and performing heating and pressurizing steps, the laminated glass 10 having a structure in which the first glass plate 11 and the second glass plate 12 are bonded via the intermediate film 13 can be obtained.
[0222] The method for manufacturing the laminated glass 10 of the present embodiment may, for example, be a step of inserting the interlayer film 13 between the first glass plate 11 and the second glass plate 12 and heating and pressurizing the interlayer film 13 after the steps of heating and shaping the first glass plate 11 and the second glass plate 12. By performing such steps, the laminated glass 10 having a structure in which the first glass plate 11 and the second glass plate 12 are bonded via the interlayer film 13 can be manufactured.
[0223] The visible light transmittance Tv of the laminated glass 10 of the present embodiment, which is defined by ISO-9050:2003 and uses a D65 light source, is preferably 70% or more. Tv is more preferably 71% or more, and further preferably 72% or more. In addition, Tv is, for example, 90% or less. That is, Tv is, for example, 70% or more and 90% or less.
[0224] The total solar transmittance Tts of the laminated glass 10 of the present embodiment, as defined by ISO-13837:2008 Convention A and measured at a wind speed of 4 m / s, is preferably 70% or less. The total solar transmittance Tts of the laminated glass 10 of the present embodiment is 70% or less, so that sufficient heat insulation can be obtained. Tts is more preferably 68% or less, and further preferably 66% or less. In addition, Tts is, for example, 55% or more. That is, Tts is, for example, 55% or more and 70% or less.
[0225] The chromaticity a of the laminated glass 10 of the present embodiment is defined by JIS Z 8781-4:2013 using a D65 light source. * It is preferably -5.0 or more, more preferably -4.0 or more, further preferably -3.0 or more, and particularly preferably -2.0 or more. * It is preferably 2.0 or less, more preferably 1.0 or less, and still more preferably 0 or less. * It is preferably -5.0 or more and 2.0 or less.
[0226] From the outside, the laminated glass 10 of the present embodiment has a chromaticity b defined by JIS Z 8781-4:2013 using a D65 light source. * It is preferably -5.0 or more, more preferably -3.0 or more, and even more preferably -1.0 or more. * It is preferably 5.0 or less, more preferably 4.0 or less, further preferably 3.0 or less, and particularly preferably 2.5 or less. * It is preferably -5.0 or more and 5.0 or less.
[0227] The glass sheet of this embodiment is * and b * Within the above range, the glass has excellent design properties as a window glass for buildings and a window glass for vehicles.
[0228] In addition, the laminated glass 10 of this embodiment is composed of c * ={(a * ) 2 +(b * ) 2} 1 / 2 The obtained c *It is preferably 4.0 or less, more preferably 3.5 or less, further preferably 3.0 or less, and particularly preferably 2.5 or less. * The lower limit of is not particularly limited, but is usually greater than 0.0. * It is preferably 0.0 or more and 4.0 or less.
[0229] The glass sheet of this embodiment is * , b * and c * Within the above range, the glass has excellent design properties as a window glass for buildings and a window glass for vehicles.
[0230] [Architectural window glass, vehicle window glass]
[0231] The window glass for building and the window glass for vehicle of the present embodiment include the above-mentioned alkali borosilicate glass. In addition, the window glass for building and the window glass for vehicle of the present embodiment may be composed of the above-mentioned laminated glass.
[0232] Hereinafter, an example in which the laminated glass 10 according to the present embodiment is used as a vehicle window glass will be described with reference to the drawings.
[0233] Figure 5 This is a conceptual diagram showing a state where the laminated glass 10 of this embodiment is installed on an opening 110 formed in the front of an automobile 100 and used as the window glass of the automobile. On the laminated glass 10 used as the window glass of the automobile, a housing (frame) 120 containing an information device and the like for ensuring the driving safety of the vehicle can be installed on the surface of the laminated glass 10 on the inner side of the vehicle.
[0234] In addition, the information device contained in the housing is a device for preventing collisions and conflicts with the vehicle ahead, pedestrians, obstacles, etc. in front of the vehicle by using cameras, radars, etc., and for notifying the driver of danger. For example, it is an information receiving device and / or an information sending device, etc., including millimeter wave radar, stereo camera, infrared laser, etc., to send and receive signals. The "signal" refers to electromagnetic waves including millimeter waves, visible light, infrared light, etc.
[0235] Figure 6 for Figure 5 The enlarged view of the S portion in FIG. 1 is a perspective view showing a portion of the laminated glass 10 in this embodiment where the housing 120 is installed. The housing 120 contains a millimeter wave radar 201 and a stereo camera 202 as information devices. The housing 120 containing the information device is usually installed on the side closer to the outside of the vehicle than the rearview mirror 150 and on the side closer to the inside of the vehicle than the laminated glass 10, but may also be installed on other portions.
[0236] Figure 7 To include Figure 6A cross-sectional view taken along the direction perpendicular to the horizontal line including the YY line. The first glass plate 11 of the laminated glass 10 is preferably arranged on the vehicle outer side. By adopting the above structure, a windshield having high stone resistance and rigidity, light weight and high gray appearance design can be realized.
[0237] Example
[0238] Hereinafter, the present invention will be specifically described with reference to Examples, but the present invention is not limited thereto.
[0239] <Production of glass plates of Examples 1 to 35>
[0240] The raw materials were put into a platinum crucible in a manner to obtain the glass composition (unit: mol%) shown in Table 1 and Table 2, and melted at a temperature of 1600°C to 1650°C for 3 hours to prepare molten glass. The molten glass was poured onto a carbon plate and slowly cooled. Both sides of the obtained plate-shaped glass were polished to obtain a glass plate with a thickness of 2.00 mm. Examples 1 to 10 are comparative examples, and Examples 11 to 35 are examples.
[0241] In Tables 1 and 2, in addition to the composition, the ratio of tricoordinate boron (B 3 [%]), the proportion of tetracoordinate boron (B 4 [%]), converted to the content of tricoordinate boron in B2O3 (B 3 asB2O3 [mol %]) and the content of tetracoordinate boron converted to B2O3 (B 4 asB2O3[mol %]), Fe-Redox, visible light transmittance Tv, solar transmittance Te, ultraviolet transmittance Tuv, chromaticity, dominant wavelength Dw, excitation purity Pe, viscosity, specific gravity, Young's modulus, average linear expansion coefficient.
[0242] The method of determining the numerical values shown in Tables 1 and 2 is shown below.
[0243] (1) Coordination number of boron:
[0244] The ratio of the coordination number of boron atoms in the glass was analyzed by NMR. The NMR measurement conditions are shown below. Measurement device: NMR device ECZ700 manufactured by NEPCO, resonance frequency: 156.38 MHz, rotation speed: 15 kHz, probe: 3.2 mm, solid flip angle: 90°, pulse repetition waiting time: 16 seconds
[0245] The single pulse method was used for measurement, and adamantane was used as an external standard (13C 28.46ppm and 37.85ppm). The measurement results were subjected to phase correction and baseline correction using NMR software Delta manufactured by JEOL Ltd., and then the ratio of tricoordinate and tetracoordinate was calculated by fitting using a Gaussian function to obtain the average coordination number.
[0246] Phase correction and baseline correction were appropriately processed by subtracting the spectrum of a blank cell that did not contain a sample. For peak fitting, a good fit was obtained by setting the peak top at 20ppm to 8ppm for tricoordinates and at 5ppm to -5ppm for tetracoordinates, and appropriately setting the peak width (in a manner such that the ratio between each coordination number is 1.5 times or less at most).
[0247] (2)Fe-Redox:
[0248] Fe-Redox is determined by the following method.
[0249] The crushed glass was decomposed using a mixture of hydrofluoric acid and hydrochloric acid at room temperature, and a certain amount of the decomposed liquid was taken into a plastic container, and hydroxylamine hydrochloride solution was added to make the Fe in the sample solution 3+ Reduction to Fe 2+ Then, 2,2'-bipyridyl solution and ammonium acetate buffer were added to make Fe 2+ Color development. The color development solution was adjusted to a certain amount using ion exchange water, and the absorbance at a wavelength of 522 nm was measured using an absorption photometer. Then, the concentration was calculated from the calibration curve prepared using the standard solution to obtain the Fe 2+ Due to the Fe 3+ Reduced to Fe 2+ , so the Fe 2+ The amount of "[Fe 2+ ]+[Fe 3+ ]”.
[0250] Next, the crushed glass was decomposed at room temperature using a mixture of hydrofluoric acid and hydrochloric acid. A certain amount of the decomposed solution was then taken into a plastic container, and 2,2'-bipyridine solution and ammonium acetate buffer were quickly added to make only Fe 2+ Color development. The color development solution was adjusted to a certain amount using ion exchange water, and the absorbance at a wavelength of 522 nm was measured using a spectrophotometer (manufactured by Hitachi, Ltd., U-4100). Then, the concentration was calculated from the calibration curve prepared using the standard solution to calculate Fe 2+ The amount of Fe 2+ The amount of [Fe 2+ ].
[0251] Then, from the above-derived [Fe 2+ ] and [Fe 2+ ]+[Fe 3+ ] Calculate Fe-Redox: [Fe 2+ ] / ([Fe 2+ ]+[Fe 3 + ]).
[0252] (3) Visible light transmittance (Tv):
[0253] Using a D65 light source, Tv when the thickness is converted to 2.0 mm was measured by the method specified in ISO-9050: 2003. Tv was measured using a spectrophotometer LAMBDA950 manufactured by PerkinElmer.
[0254] (4) Solar transmittance (Te):
[0255] The solar energy transmittance Te is a solar energy transmittance obtained by measuring and calculating the transmittance using a spectrophotometer LAMBDA950 manufactured by PerkinElmer according to the provisions of ISO-9050:2003.
[0256] (5) Ultraviolet transmittance (Tuv):
[0257] Tuv when the thickness is converted to 2.0 mm was measured by the method specified in ISO-9050: 2003. Tuv was measured using a spectrophotometer LAMBDA950 manufactured by PerkinElmer.
[0258] (6) Chroma (L * ,a * ,b * ,c * ):
[0259] The chromaticity L defined by JIS Z 8781-4:2013 was measured using D65 light source * ,a * ,b * . The obtained a * ,b * Substitute the value of into the following formula to find c * .
[0260] c * ={(a * ) 2 +(b * ) 2} 1 / 2
[0261] (7) Dominant wavelength (Dw):
[0262] The dominant wavelength Dw of the transmitted light is the dominant wavelength of the transmitted light calculated in accordance with JIS Z 8701:1999.
[0263] (8) Excitation purity (Pe):
[0264] The excitation purity Pe is the excitation purity calculated in accordance with JIS Z 8701:1999.
[0265] (9) Viscosity:
[0266] The viscosity η, which is a criterion for bending workability, was measured by the cantilever beam bending method and reached 10 11 Temperature T at dPa·s 11 and viscosity η reaches 10 12 Temperature T at dPa·s 12 .
[0267] (10) Specific gravity:
[0268] A glass block of about 20 g without containing bubbles cut out from a glass plate was measured by the Archimedean method.
[0269] (11) Young's modulus:
[0270] The elastic modulus of fine ceramics was measured at 25° C. by an ultrasonic pulse method (Olympus, DL35) based on JIS R1602:1995.
[0271] (12) Average linear expansion coefficient (CTE) in the range of 50℃ to 350℃ 50-350 ):
[0272] The dilatometer (TMA) was used for measurement and the value was obtained in accordance with JIS R3102:1995.
[0273] The measurement results are shown in Tables 1 and 2. In Tables 1 and 2, "-" indicates that calculation was not possible due to the absence of B2O3, and a blank column indicates that the measurement was not performed.
[0274]
[0275]
[0276] The glasses of Examples 11 to 35 as embodiments have a solar transmittance Te of 90% or less, a main wavelength Dw of 520 nm to 574 nm, and an excitation purity Pe of 4.0% or less, and have excellent heat shielding properties while exhibiting good design properties.
[0277] On the other hand, the glass of Example 1 as a comparative example does not contain B 2 O 3 , and therefore has a dominant wavelength Dw of 500 nm, and is inferior in design properties compared to the examples.
[0278] In addition, the glass of Example 2 as a comparative example has a solar transmittance Te of 93% because the Fe2O3 content is less than 0.03% and the proportion of tricoordinate boron is greater than 61%, and its thermal insulation is poor compared with the examples.
[0279] In addition, since the ratio of tricoordinate boron in Examples 3, 7 to 9 as comparative examples is greater than 61%, the main wavelength Dw is greater than 574 nm, and the appearance design is inferior to that of the examples.
[0280] In addition, since the ratio of tricoordinate boron in Examples 4 to 6 as comparative examples is greater than 61%, the main wavelength Dw is greater than 574 nm and the excitation purity Pe is greater than 4.0%, and the appearance design is inferior to that of the examples.
[0281] In addition, the glass of Example 10 as a comparative example has a solar transmittance Te of 91% because the Fe2O3 content is less than 0.03%, and its heat insulation property is inferior to that of the embodiment.
[0282] Although the present invention is described in detail with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on Japanese patent application (Japanese patent application 2022-099058) filed on June 20, 2022, the contents of which are incorporated herein by reference.
[0283] Description of symbols
[0284] 10Laminated glass
[0285] 11 First Glass Plate
[0286] 12 Second Glass Plate
[0287] 13Intermediate film
[0288] 100 cars
[0289] 110 opening
[0290] 120 Shell
[0291] 150 rearview mirror
[0292] 201 millimeter wave radar
[0293] 202 Stereo Camera
[0294] 300 radio waves
Claims
1. An alkali borosilicate glass, wherein: The alkali borosilicate glass has a total iron content calculated as Fe2O3 of 0.03% or more, based on mole % of oxides. The ratio of tricoordinate boron to the total amount of tricoordinate boron and tetracoordinate boron is 61% or less. The alkali borosilicate glass contains substantially no Se and CoO. When the thickness is converted to 2.0 mm, the solar transmittance Te of the alkali borosilicate glass specified by ISO-9050:2003 is less than 90%, the main wavelength Dw of the alkali borosilicate glass measured by the standard C light source specified by JIS Z 8701:1999 is greater than 520 nm and less than 574 nm, and the excitation purity Pe of the alkali borosilicate glass measured by the standard C light source specified by JIS Z 8701:1999 is less than 4.0%.
2. The alkali borosilicate glass according to claim 1, wherein: When the thickness is converted to 2.0 mm, the ratio (Tv / Te) of the visible light transmittance Tv of the alkali borosilicate glass defined by ISO-9050:2003 and the solar energy transmittance Te of the alkali borosilicate glass defined by ISO-9050:2003 using a D65 light source is 1.05 or more.
3. The alkali borosilicate glass according to claim 1, wherein: When the thickness is converted to 2.0 mm, the visible light transmittance Tv of the alkali borosilicate glass defined by ISO-9050:2003 obtained using a D65 light source is 75% or more.
4. The alkali borosilicate glass according to claim 1, wherein: When the thickness is converted to 2.0 mm, the visible light transmittance Tv of the alkali borosilicate glass defined by ISO-9050:2003 obtained using a D65 light source is less than 75%.
5. The alkali borosilicate glass according to claim 1, wherein: The content of total iron in the alkali borosilicate glass calculated as Fe2O3 is 0.040% or more and 0.60% or less, in terms of mol% based on oxides.
6. The alkali borosilicate glass according to claim 1, wherein: The alkali borosilicate glass has a Young's modulus of 65 GPa or more.
7. The alkali borosilicate glass according to claim 1, wherein: Glass viscosity reaches 10 11 [dPa·s] at temperature T 11 Below 640°C.
8. The alkali borosilicate glass according to claim 1, wherein: In terms of mole % based on oxides, the alkali borosilicate glass comprises: 70%≤SiO2≤80% 8.0%≤B2O3≤20% 1.0%≤Al2O3≤5.0% 0.0%≤Li2O≤5.0% 2.0%≤Na2O≤10% 0.0%≤K2O≤5.0% 0.0%≤MgO≤5.0% 0.0%≤CaO≤5.0% 0.0%≤SrO≤5.0% 0.0%≤BaO≤5.0% SiO2+B2O3+Al2O3≥89% Li2O+Na2O+K2O≥5.0%.
9. The alkali borosilicate glass according to claim 8, wherein: The content of total iron converted to Fe2O3 in the alkali borosilicate glass is greater than or equal to 0.040% and less than or equal to 0.60% in terms of mol% based on oxides, and the mass proportion of divalent iron converted to Fe2O3 in the total iron converted to Fe2O3 is greater than or equal to 10%.
10. The alkali borosilicate glass according to claim 8, wherein: The alkali borosilicate glass contains Li2O.
11. A curved glass, wherein: The curved glass comprises the alkali borosilicate glass according to claim 1 .
12. A laminated glass, wherein: The laminated glass comprises a first glass plate, a second glass plate, and an intermediate film sandwiched between the first glass plate and the second glass plate. The first glass plate is the alkali borosilicate glass according to any one of claims 1 to 10 or the bent glass according to claim 11.
13. The laminated glass according to claim 12, wherein: The second glass plate is the alkali borosilicate glass according to any one of claims 1 to 10 or the bent glass according to claim 11.
14. The laminated glass according to claim 12, wherein: The second glass plate is an alkali aluminosilicate glass containing 1.0% or more of Al 2 O 3 in terms of molar percentage on an oxide basis.
15. The laminated glass according to claim 12, wherein: The second glass plate is an alkali-aluminoborosilicate glass containing 1.0% or more of Al2O3 and 1.0% or more of B2O3 in terms of molar percentage on an oxide basis.
16. The laminated glass according to claim 12, wherein: The second glass plate is chemically strengthened glass.
17. The laminated glass according to claim 12, wherein: The second glass sheet is soda lime glass.
18. A vehicle window glass, wherein: The vehicle window glass comprises the alkali borosilicate glass according to any one of claims 1 to 10 or the bent glass according to claim 11 .
19. A vehicle window glass, wherein: The vehicle window glass comprises the laminated glass according to claim 12 .
20. A window glass for building, wherein: The building window glass comprises the alkali borosilicate glass according to any one of claims 1 to 10 or the bent glass according to claim 11 .
Citation Information
Patent Citations
Colored glass
JP1992280834A
Uv light-absorbing gray glass
JP1995109147A
Ultraviolet ray absorbing gray glass
JP1997301736A
Glass with dark gray color
JP2001019470A
Partition
JP2022099058A